Doing Business in South East Europe 2011 - World Bank; International Finance Corporation (Washington, DC, 2013)
Doing Business in South East Europe 2011 is the second subnational report of the Doing Business series in South East Europe. In 2008, quantitative indicators on business regulations were created for 22 cities in 7 economies: Albania, Bosnia and Herzegovina, Croatia, Kosovo, FYR Macedonia, Montenegro, and Serbia. This report is the result of collaboration between International Finance Corporation (IFC) Southern Europe investment climate advisory services and the subnational doing business team of the global indicators and analysis department, World Bank Group. The report was produced with the financial support of the Government of Switzerland through the State Secretariat for Economic Affairs (SECO), the Government of Austria, and the United States Agency for International Development (USAID). The paper includes the following headings: starting a business, dealing with construction permits, enforcing contracts, registering property, doing business indicators, data notes, and city tables.